Study of oviposition and host plant finding of tomato leaf miner, Tuta absoluta (Lep.:Gelechiidae) in laboratory conditions - E. Tamoli Torfi; A. A. Seraj; A. Rajabpour (نامه انجمن حشره‌شناسی ایران, 2017)
Tomato leaf miner, Tuta absoluta (Meyrick) is a key and dangerous pest of Solanaceous plants in Iran.  Larvae of the pest cause damage on different parts of host plants including leaves, stems, and fruits. In this study, the oviposition and host plant finding of tomato leaf miner on four important plants of Solanaceae including tomato, potato, eggplant, and pepper were investigated at laboratory conditions. Based on the results, mean egg numbers of the pest on the leaves of tomato, potato, eggplant and pepper were 32.20, 17.20, 6.40, and 3.00, respectively, which were the highest on tomato and the lowest on eggplant and pepper. Furthermore, the mean egg numbers of the pest on the upper surface of the leaves of tomato was the highest in compar with the other treatments.   According to the olfactometer test, host plant finding of the females was the highest on tomato. So, tomato was the most preferred host plant for the adult moths among the tested host plants. The results of the present study can be used in integrated pest management programs of this pest.